Pola Pembagian Waris dalam Masyarakat Sungai Musi: Analisis Fenomenologis terhadap Praktik Adat dan Pilihan Rasional - Muna, Nailal (JOM, 2024)
This study examines inheritance distribution patterns among the communities along the Musi River in South Sumatra, who are known for adhering to customary law systems with patrilineal and majorat patterns. However, variations in inheritance practices that do not always align with customary traditions have been observed. Using a phenomenological approach and rational choice theory analysis, this study identifies inheritance distribution patterns and the factors influencing community preferences. The findings reveal three main patterns: (1) pure customary patterns that prioritize paternal lineage and male heirs, (2) compromise patterns combining customary law with Islamic law or family agreements, and (3) individualistic patterns based on personal agreements among heirs without reference to specific legal systems. Factors influencing these preferences include emotional closeness between heirs and inheritors, economic considerations to preserve family assets, and principles of mutualism in maintaining social relationships. This study provides insights into the dynamics of customary law adaptation amid social and economic changes in the Musi River communities